The Role of Transformational Leadership Behaviours’ Effects on Corporate Entrepreneurship Behaviours and Financial Performance of Firms - Ocak, Metin; Ozturk, Alperen (International Review of Management and Marketing, 2018)
This study was conducted in order to determine the relationship between organizational managers’ transformational leadership and organizations’corporate entrepreneurial behaviours and the effects of both on financial performance. For this purpose, a hierarchical regression analysis was executed on the data collected from 121 managers who work in some manufacturing industry firms operating in Turkey. Results of the hierarchical regression analysis showed that transformational leadership behaviours of the managers have an effect on the corporate entrepreneurship behaviours and financial performance of the organizations. In addition to this, it was found that corporate entrepreneurship behaviours had significant effects on financial performance of organizations. In this context, the relations revealed of theoretical background are generally supported and findings were discussed in the light of the literature. Keywords: Transformational Leadership, Corporate Entrepreneurship, Financial Performance, Manufacturing Industry Firms, Hierarchical Regression Analysis JEL Classifications: L25, L26, M12